2008
DOI: 10.1177/0003319708325450
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific Effects of Calcitonin Gene-related Peptide and Substance P on Coronary Blood Flow in an Experimental Model

Abstract: CGRP plays similar roles as a vasodilator in males and females. SP seems to act as a vasoconstrictor in females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
(16 reference statements)
0
2
0
2
Order By: Relevance
“…W niniejszym doświadczeniu nie stwierdzono takich włókien ani w warunkach fizjologicznych, ani po podaniu bisfenolu A. Natomiast wcześniejsze badania wykazały stosunkowo dużą ilość CGRP-pozytywnych struktur nerwowych w innych częściach mięśnia sercowego (8,31,35). Ponadto wiadomo, iż CGRP jest ważnym czynnikiem regulującym pracę serca, który między innymi bierze udział w kontroli przepływu krwi przez naczynia wieńcowe oraz wykazuje działanie inotropowo-dodatnie oraz kardioprotekcyjne (11,21). Opisane powyżej różnice sugerują, że unerwienie koniuszka serca wykorzystuje nieco odmienne mechanizmy i substancje aktywne niż struktury nerwowe kontrolujące inne części mięśnia sercowego.…”
Section: Cgrp)unclassified
See 1 more Smart Citation
“…W niniejszym doświadczeniu nie stwierdzono takich włókien ani w warunkach fizjologicznych, ani po podaniu bisfenolu A. Natomiast wcześniejsze badania wykazały stosunkowo dużą ilość CGRP-pozytywnych struktur nerwowych w innych częściach mięśnia sercowego (8,31,35). Ponadto wiadomo, iż CGRP jest ważnym czynnikiem regulującym pracę serca, który między innymi bierze udział w kontroli przepływu krwi przez naczynia wieńcowe oraz wykazuje działanie inotropowo-dodatnie oraz kardioprotekcyjne (11,21). Opisane powyżej różnice sugerują, że unerwienie koniuszka serca wykorzystuje nieco odmienne mechanizmy i substancje aktywne niż struktury nerwowe kontrolujące inne części mięśnia sercowego.…”
Section: Cgrp)unclassified
“…Ponadto SP uczestniczy w regulacji przepływu krwi przez naczynia wieńcowe (21,35) oraz pobudza unerwienie cholinergiczne serca, powodując ujemny efekt ino-, batmo-i chronotropowy (11). W warunkach eksperymentalnych SP może oddziaływać stymulująco na wzrost i rozwój kardiomiocytów (9).…”
Section: Cgrp)unclassified
“…In particular, SP influences cardiomyocyte activity through the activation of cholinergic innervation and causes bradycardia [55,56]. Moreover, SP regulates the blood flow in vessels located in the heart wall (the character of this impact depends on gender) [57,58] and may stimulate the growth of cardiomyocytes [59] and influence the heart mast cells, stimulating the release of pro-inflammatory factors [60][61][62]. It is also known that SP participates in mechanisms connected with various heart diseases, including viral and parasitic infections, heart ischemia and cardiac fibrosis [54,59].…”
Section: Discussionmentioning
confidence: 99%
“…As a member of the neurotransmitter tachykinin family, substance P (SP) is widely distributed in the nervous system and peripheral organs and tissues and is involved in pain reaction, immune regulation, inflammatory reaction, and wound healing [25]. SP can effectively combat the elevation of blood pressure caused by norepinephrine and angiotensin II (Ang II) and also can lower blood pressure, relax blood vessels, and increase blood flow volume in a short time [6]. Studies have indicated that SP could inhibit the damaging effect of norepinephrine on myocardial cells in acute myocardial ischemia reperfusion, while its effect on myocardial remodeling and its role in the process of fibrosis are not entirely clear [7].…”
Section: Introductionmentioning
confidence: 99%